Industri Kreatif sebagai Basis Kearifan Lokal dan Penguatan Pariwisata Berkelanjutan - Tetty Tiurma Uli Sipahutar; Tri Martial; Ahmad Rizki Harahap; Jhon Piter; Benny Rojeston Marnaek Nainggolan; Ninta Katharina; Deasy Arisandy Aruan; Ina Namora Putri Siregar (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
Sustainable tourism development in Sipirok, South Tapanuli, requires a stronger connection between local creative products, community institutions, and destination branding. This community service article aims to describe the empowerment process for developing local-wisdom-based creative industries in Desa Situmba Julu and the Kawah Balerang ecotourism area. The program used a participatory empowerment method consisting of pre-implementation mapping, implementation through socialization, focus group discussion, product curation, and post-activity evaluation. Data were collected through observation, partner discussion, documentation, and reflection on program outputs. The activity produced five measurable outputs: identification of local creative assets, mapping of partner problems, curation of souvenir products such as T-shirts, caps, and key chains, formulation of BUMDes Marsada Mahita as an aggregator of production and promotion, and an integrative empowerment model linking local wisdom, creative products, digital branding, institutional strengthening, and sustainable tourism. The findings show that community actors already possess initial creative assets but still need assistance in product standardization, brand narration, cataloguing, inventory recording, and market distribution. The contribution of this program lies in transforming a conceptual tourism development model into a practical community-service model that can be replicated in tourism villages with similar natural and cultural resources.